Narciclasine inhibits phospholipase A2 and regulates phospholipid metabolism to ameliorate psoriasis-like dermatitis - Kong, Yi; Jiang, Jian; Huang, Yuqiong; Liu, Xin; Jin, Zilin; Li, Li; Wei, Fen; Liu, Xinxin; Yin, Jie; Zhang, Yonghui; Tong, Qingyi; Chen, Hongxiang (Frontiers in Immunology, 2023)
Introduction Psoriasis is a common inflammatory skin disease recognized by the World Health Organization as "an incurable chronic, noninfectious, painful, disfiguring and disabling disease." The fact that metabolic syndrome (MetS) is the most common and important comorbidities of psoriasis suggests an important role of lipid metabolism in the pathogenesis of psoriasis. Narciclasine (Ncs) is an alkaloid isolated from the Amaryllidaceae plants. Its biological activities include antitumor, antibacterial, antiinflammatory, anti-angiogenic and promoting energy expenditure to improve dietinduced obesity. Here, we report that Ncs may be a potential candidate for psoriasis, acting at both the organismal and cellular levels. Methods The therapeutic effect of Ncs was assessed in IMQ-induced psoriasis-like mouse model. Then, through in vitro experiments, we explored the inhibitory effect of Ncs on HaCaT cell proliferation and Th17 cell polarization; Transcriptomics and lipidomics were used to analyze the major targets of Ncs; Single-cell sequencing data was used to identify the target cells of Ncs action. Results Ncs can inhibit keratinocyte proliferation and reduce the recruitment of immune cells in the skin by inhibiting psoriasis-associated inflammatory mediators. In addition, it showed a direct repression effect on Th17 cell polarization. Transcriptomic and lipidomic data further revealed that Ncs extensively regulated lipid metabolismrelated genes, especially the Phospholipase A2 (PLA2) family, and increased antiinflammatory lipid molecules. Combined with single-cell data analysis, we confirmed that keratinocytes are the main cells in which Ncs functions. Discussion Taken together, our findings indicate that Ncs alleviates psoriasiform skin inflammation in mice, which is associated with inhibition of PLA2 in keratinocytes and improved phospholipid metabolism. Ncs has the potential for further development as a novel anti-psoriasis drug.